PELATIHAN OPTIMALISASI BRANDING/MEREK DAN DIGITALISASI UMKM DI NAGARI SAWAH LAWEH KABUPATEN PESISIR SELATAN - Malik, David; Yulihardi, Yulihardi; Suandi, Edi (Diklat Review : Jurnal manajemen pendidikan dan pelatihan, 2024)
This community service program aims to enhance the branding and digital skills of Micro, Small, and Medium Enterprises (MSMEs) in Nagari Sawah Laweh, Pesisir Selatan Regency. In today’s digital era, strong branding and an online presence are critical for MSMEs to remain competitive and expand their market reach. This program includes training sessions focused on effective branding strategies, the use of digital platforms for business, and practical steps to establish a sustainable online presence. Participants will be introduced to essential digital tools and social media marketing techniques that can help them increase visibility and strengthen customer engagement. The outcomes of this program are expected to boost the entrepreneurial capacity of local MSMEs, empowering them to compete in the broader market while fostering regional economic growth. This initiative also aims to foster a digitally empowered MSME community that can adapt to rapid technological advancements and capitalize on digital opportunities. Keywords: MSMEs, Branding, Digitalization, Social Media Marketing, Nagari Sawah Laweh